Promosi dan Mutasi Dalam Perkembangan Karir - Ega Leovani; Catharina Clara (Faculty of Economics and Business, Universitas Stikubank, 2022)
Mutations and promotions are things that often occur in a company environment. Position transfers and promotions are intended to be able to provide encouragement to employees to be able to contribute in the form of good performance expected by the organization and can improve the abilities, skills, skills and knowledge of employees which will later be utilized in fulfilling the career development needs of employees. Job transfer and promotion programs can be carried out in all forms and sizes of organizations including a university. XYZ University has several times conducted transfer and promotion programs. In this study, we will see whether transfers and promotions have an influence on employee career development in XYZ University. The sample taken is employees who have received mutations or promotions with a total of 68 people. From the results of data processing, it is proven that there is an effect of Position Mutation and Job Promotion on the career development of employees in XYZ University.